Heterogeneous consumers, segmented asset markets, and the effects of monetary policy - Zeno Enders (University of Heidelberg, Department of Economics, 2012)
This paper examines how segmented asset markets can generate real and nominal effects of monetary policy. I develop a model, in which varieties of consumption bundles are purchased sequentially. Newly injected money thus disseminates slowly through the economy via second-round effects and induces a longer-lasting, non-degenerate wealth distribution. As a result, the demand elasticity differs across consumers, affecting optimal markups chosen by producers. The model predicts a short-term inflation-output trade-off, a liquidity effect, countercyclical markups, and procyclical wages and expenditure dispersion across consumers after monetary shocks. Including a modest degree of real or nominal wage rigidity yields responses that are also quantitatively in line with empirical evidence.
urn:nbn:de:bsz:16-heidok-142596
Keywords: 330; Segmented Asset Markets; Monetary Policy; Countercyclical Markups; Liquidity Effect; Expenditure Dispersion